NONPENETRATING ABDOMINAL INJURIES - Brock, William (1956)
Nonpenetrating abdominal injuries are commonly seen in a general hospital. High speed traffic accidents are responsible for the majority of these injuries. The mortality rate is high. Deaths were from associated injuries, failure to recognize abdominal trauma, hemorrhage and from acute renal insufficiency. Careful observation of every severely injured person, vigorous treatment of hemorrhagic shock with whole blood, and prompt surgical intervention when indicated will improve the mortality figures.